Peningkatan Hasil Belajar Melalui Penerapaan Model Icare Pada Siswa Kelas Viia Smp Negeri 3 Makassar - Abdul Hadi (Universitas Islam Ahmad Dahlan (UIAD) Sinjai, 2022)
This research was classroom action research that aimed to empower teachers in solving learning problem in school in order to improve the quality of learning. This research was carried out for two cycles. The first cycles consisted of 4 meetengs and the second cycle also consisted of 4 meetengs The instruments used in this research was the end of cycle tes to measure mathematical reasoning ablity by using ICARE learning model, student response questionnaires, and learning implementation observation guidelines which were analyzed qualitatively and quantitatively with the strongest documentation results. The result of this research indicated that mathematical reasoning ablity at the seventh grade students pf SMP Negeri 3 Makassar has increased from cycle 1 to cycle 2 after carrying out the learning process with ICORE learning model. Judging from the average score of the overall reasoning indicators in cycle 1 was 34,8 with a standar deviation of 14,456 and increase in cycle 2 to 84,28 with a standar deviation 10.147. Completeness obtained by students in cycle 1 with a percentage of 33,33% then increased in cycle 2 with a percentage of students who completed 86,66%. So in this research it was concluded that applying ICARE learning model can improve studnts”s mathematical reasoning ablitiy at the seventh grade students of SMP Negeri 3 Makassar.